(untitled) (Revista de Artes Marciales Asiáticas, 2023)
Chan chuang, a psychophysical practice renowned for its beneficial effects, has been favored by martial artists and traditional Chinese medicine practitioners since ancient times. With the onset of the COVID-19 pandemic, chan chuang has garnered increased attention and recognition. However, existing research primarily focuses on the efficacy of chan chuang, rather than exploring the practice itself. Consequently, there is a dearth of scientific and experiential guidance available to current practitioners of chan chuang. To address this gap, the present study employs an in-depth interview method within a qualitative research framework, conducting follow-up interviews with eight martial artists who regularly engage in chan chuang practice. By gaining insights into the physical and mental states of these practitioners, this paper aims to elucidate their embodied experiences of chan chuang from the perspective of “body perception”. The findings reveal that the practitioners’ perception of their bodies during chan chuang practice can be characterized by three key aspects: stillness, naturalness, and qi. The sense of stillness signifies a state of tranquility in both body and mind. The sense of naturalness represents a harmonious equilibrium of body and mind, at times even resulting in a loss of self-awareness. Finally, the sense of qi conveys a serene mental state accompanied by the smooth flow of life energy and blood. These three dimensions guide chan chuang practitioners toward attaining physical and mental well-being.